A Retrospective Review of Outcomes of Dental Treatment Performed for Special Needs Patients under General Anaesthesia: 2-Year Follow-Up - Sreekanth Kumar Mallineni; Cynthia Kar Yung Yiu (The Scientific World Journal)
Objective. The purpose of the study was to evaluate the follow-up pattern of special needs patients (SNP) treated under general anaesthesia (GA) and the failure rates of different treatment procedures and restorative materials. Study Design. The treatment records of the patients who received dental treatment under GA during 2005 to 2009 were reviewed. The duration of follow-up periods, the outcomes of different treatment procedures, and the quality of different restorative materials were recorded and evaluated. Statistics were used for the comparison (SPSS 20.0). Pearson’s chi-square test and post hoc analysis were used to evaluate the attendance of postoperative appointments and the associations of failure rates of different treatment procedures and restorative materials. Cohen kappa statistics was used for intraexaminer reliability. Results. A total of 177 patients were included in the study. The attendance of postoperative appointments showed a gradual decrease from 96% to 36% within 24 months (P<0.05). Restorative procedures had the highest failure rates among all treatment procedures (P<0.05). Stainless steel crowns showed higher survival rates among different restorative materials (P<0.05). Pulp treatment in primary molars has higher success rate than primary incisors and canines. Composite restorations placed in primary canines have low survival rates. The intraexaminer reliability was good (k=0.94). Conclusion. The attendance for postoperative follow-up appointments declined within two years. Restorative treatment was less successful when compared to preventive and pulp treatments. Stainless steel crowns were more reliable restorations with higher survival rates and composite restorations were less durable.